A Long-Term Conserved Satellite DNA That Remains Unexpanded in Several Genomes of Characiformes Fish Is Actively Transcribed - Dos Santos, Rodrigo Zeni [UNESP]; Calegari, Rodrigo Milan [UNESP]; Silva, Duílio Mazzoni Zerbinato de Andrade [UNESP]; Ruiz-Ruano, Francisco J.; Melo, Silvana [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Uliano-Silva, Marcela; Porto-Foresti, Fábio [UNESP]; Utsunomia, Ricardo [UNESP] (Oxford University Press (OUP), 2021)
Eukaryotic genomes contain large amounts of repetitive DNA sequences, such as tandemly repeated satellite DNAs (satDNAs). These sequences are highly dynamic and tend to be genus- or species-specific due to their particular evolutionary pathways, although there are few unusual cases of conserved satDNAs over long periods of time. Here, we used multiple approaches to reveal that an satDNA named CharSat01-52 originated in the last common ancestor of Characoidei fish, a superfamily within the Characiformes order, ∼140-78 Ma, whereas its nucleotide composition has remained considerably conserved in several taxa. We show that 14 distantly related species within Characoidei share the presence of this satDNA, which is highly amplified and clustered in subtelomeric regions in a single species (Characidium gomesi), while remained organized as small clusters in all the other species. Defying predictions of the molecular drive of satellite evolution, CharSat01-52 shows similar values of intra- and interspecific divergence. Although we did not provide evidence for a specific functional role of CharSat01-52, its transcriptional activity was demonstrated in different species. In addition, we identified short tandem arrays of CharSat01-52 embedded within single-molecule real-time long reads of Astyanax paranae (536 bp-3.1 kb) and A. mexicanus (501 bp-3.9 kb). Such arrays consisted of head-to-tail repeats and could be found interspersed with other sequences, inverted sequences, or neighbored by other satellites. Our results provide a detailed characterization of an old and conserved satDNA, challenging general predictions of satDNA evolution.
Keywords: neotropical fish; repetitive DNA; satDNA; tandem repeats